MODEL NON LINEAR KEJADIAN CURAH HUJAN EKSTRIM DI KOTA PALU MENGGUNAKAN PROGRAM JAVA - Nurrahmi, Sitti; Farhamsa, Dedy; Iqbal, Iqbal (Universitas Islam Negeri Alauddin Makassar, 2020)
Weather and climate are the main factors for influence on various activities of life. The increasing of human activity has made the change in components biophisical environment, which are major contributors about climate change. The most important of the process of climate change is the emergence of the extreme, that one example is, extreme rainfall, that the rainfall have more than 50 mm intensity / day. To know characteristic of climate change occurring, needed a model who represented data rainfall in various meteorology station. Based on it, author make a modeling the extreme rainfall in Palu city using Java programming. The results of the extreme rainfall predictions 10 years using software models and Java programming, in Palu city with using fourier series function order 5 predicted the extreme rainfall will likely increase every year with the highest event areÂ 2 times / years. The prediction was featuring the preciselyÂ value with the real data. So, we can conclude that the extreme rainfall model tends to be accurate and can be used to predict the extreme rainfall in Palu city and in other cities.